Study of multi-mode forcing effects on coherent structures of flow transition in a compressible jet - Cong Xu (AIP Publishing LLC, 2021)
The disturbances added to trigger turbulence in the simulation of jet flows are mostly implemented with multiple azimuthal modes. The validity and rationale of using such multi-modes are still not very clear. In this paper, large eddy simulations are performed to study a compressible isothermal jet. Flow forcing methods for promoting transition are considered. Two multi-mode disturbances and a single-mode excitation are shown to trigger rapid flow transition, but the development of mixing layers in downstream varies. The most organized vortical structures produced by the vortex rolling/pairing process are observed when the jet is excited by the single-mode forcing, while the shear layers are closer to turbulence when the two multi-mode disturbances are employed. In order to unveil the mechanism behind such differences, dynamic mode decompositions on the axial velocity are conducted to analyze the spatiotemporal coherent structures. The results show that near the nozzle exit, the multi-mode disturbances have triggered more high frequency coherent structures, while the single-mode forcing has produced both low and high frequencies. The low frequency components are transmitted downstream of the jet, leading to poor prediction of the turbulent flow properties.